O materialismo lacaniano encontra The Waste Land : real, imaginário e o papel da ideologia - Grecca, Gabriela Bruschini (2016)
This study aims to explore some elements of the poem The Waste Land (1922), by T.S. Eliot, with the theoretical mediation of Slavoj i ek's Lacanian Materialism, critical current in Brazil that has recently been appropriated by researchers, such as Marisa Correa Silva, to establish analysis in the field of Literary Studies. The hypothesis developed in the study is that it is possible to elucidate how the innovative aesthetic structure of the poem is in tension with a conservative social structure not systematized, as there is a Western Imaginary sustained by the poem which hides a movement called "escape from the Real". The Real, in this paper, should not be understood as synonymous with reality, but as the excess that escapes and resists reality. The term, coined by psychoanalyst Jacques Lacan, was appropriated by philosopher Slavoj i ek, and, in The Waste Land, it can be seen in the constant repetition of scenes in which the fantasy that sustains a given situation (supported by Imaginary) threatens to burst and question the existing order. However, it always returns to the previous time and remains an abandoned or unfinished idea. This inertia is evident to the reader of the poem, but the goal of the analysis is to demonstrate that it can only exist because there is a full cyclic movement of escape from the Real, of a fantasy returning to itself and false activities that guarantee the absence of changes and make the order of appearances remain still. It is believed that this thesis is important to bring a new perspective to the critical studies of this poem (considered one of the greatest of the twentieth century), which have been discussing about the apology or refusal towards modern time in The Waste Land, considering mainly if its ellusive end transmits an optimistic or pessimistic approach to the future of humanity. With the help of Lacanian materialism, it was observed that reaching a solution to this debate is a pitfall, and that the life of the poem remains in the tension between inversions that are empty from oppositions, i.e. investments that end up as ways of referring the same issue, so that what the poem denounces become what he preaches, and the transcendence of the corrupt world sought by the course of the five sections end up, in the words of i ek (2013), with the feeling of a metaphysical malaise.